SPORULATION OF CLOSTRIDIUM BOTULINUM I. : Selection of an Aparticulate Sporulation Medium - Tsuji, Kiyoshi (1962)
Tsuji, Kiyoshi (National Canners Association Research Laboratory, Berkeley, Calif.) and William E. Perkins. Sporulation of Clostridium botulinum I. Selection of an aparticulate sporulation medium. J. Bacteriol. 84:81–85. 1962.—The thermal resistances of Clostridium botulinum spores produced in seven different liquid media were compared. A 5% solution of a commercially produced mixture of dehydrated enzymatic hydrolyzates of casein and animal tissues yielded spores of maximal thermostability. Sporulation in this medium was almost complete under the conditions employed. The suspensions were essentially free of vegetative cells and sporangia and could be thoroughly washed. The incubation time at 30 C was found to have a negligible effect on thermal resistance for periods between 4 and 21 days. Supplementing the medium yielding the most thermolabile spores with various divalent cations did not enhance the thermal resistance of the spores produced. The identical amino acids and related compounds were found in spores exhibiting the maximal and minimal thermal resistance when they were analyzed chromatographically. The more thermostable spores contained a higher concentration of glucosamine.